Does a “liquidity trap” exist today (2009) and does it matter? - Artzer, Steven P. (Kansas State University, 2009)
Can stimulative monetary policy be effective when there is a “liquidity trap”? This question surfaced during the Great Depression and is raising its head again today due to the current financial crisis. A definitive answer never materialized for the 1930’s, as differences of opinion between non-monetarist and monetarist economists arose about this issue. This need not be the case today. In this thesis I will first enumerate several different meanings of the term “liquidity trap” and their implications for monetary policy. Then, with data from the Federal Reserve, I will attempt to validate the likelihood of a liquidity trap. I do this for the demand for money and bank liquidity traps. I use regression analysis over a fifteen year period with varying interest rates to determine if the elasticities of demand increase as interest rates fall, indicating a liquidity trap. My use of log linear regressions for both demand for money and bank liquidity traps, using data from the present financial crisis, adds to the evidence supporting the liquidity hypothesis, but does not empirically establish the existence of a liquidity trap. Following my findings, I detail actions taken by the Federal Reserve and show the subsequent results through the summer and into the fall of 2009. From this, I make a conclusion that the United States is most likely in a liquidity trap and it does matter.
Keywords: Liquidity trap; Bank reserves; Economics, Theory (0511)